Optimalisasi Pengumpulan Dana Zakat melalui Strategi Fundraising Badan Amal Zakat Nasional: Studi Manajemen Filantropi Islam - Farid Ardhy Sudirman; Annas Ma’ruf; Hudan Ngisa Anshori; Denny Rakhmad Widi Ashari (Universitas Nahdlatul Ulama Blitar, 2026)
This study aims to analyze the fundraising strategies implemented by the National Zakat Agency (BAZNAS) to optimize the collection of zakat funds through an Islamic philanthropy management approach. As an Islamic social finance instrument, zakat plays a crucial role in improving community welfare, reducing poverty, and supporting equitable economic development. However, the significant potential of national zakat has not yet been fully matched by the optimization of zakat collection by zakat management institutions. This study employs a descriptive-qualitative method using a library research approach, involving the review of various books, scientific journals, official reports, and regulations related to zakat management in Indonesia. The findings indicate that BAZNAS’s fundraising strategies are implemented through digital fundraising, social-religious campaigns, strengthening zakat literacy, institutional collaboration, and enhancing transparency and public accountability. These strategies have proven effective in increasing public trust and the loyalty of zakat contributors, thereby leading to an increase in zakat collection. Additionally, the application of digital technology facilitates access to services and expands the reach of zakat collection in the digital era. From the perspective of Islamic philanthropy management, fundraising is not only oriented toward raising funds but also toward fostering spiritual awareness and social solidarity within the community. This study confirms that the integration of digital technology, professional governance, and Sharia values are key factors in the development of effective, transparent, and sustainable zakat management in Indonesia.